Do travel clinic visitors read information on sexual risk abroad in travel health brochures?. Issue 1 (January 2017) - Croughs, Mieke; de Gouw, Annemarie; Remmen, Roy; Van den Ende, Jef
Background: A substantial proportion of travel clinic visitors have sexual encounters while abroad. Hence, guidelines on travel health recommend discussing sexual risk in a pre-travel consultation. However, previous studies showed that it often is not discussed. Although travel clinic visitors usually do receive written information on sexual risk abroad, few data are available on whether this information is read. Therefore, this prospective cohort study in travel clinic visitors was performed. Methods: Travel clinic visitors were invited to complete a questionnaire after return from their journey. Results: A total of 130 travellers (55%) responded. Half of them recorded they read the information on sexual risk. Male gender (OR 9.94 95% CI 3.12 – 31.63) and 'travelling with others' (OR 2.7 95% CI 1.29 – 5.78) were significant independent predictors of reading the information on sexual risk. High risk travellers, i.e. those travelling without a steady partner, were less likely to have read it. Although websites and apps were mentioned as better methods of providing information, none of the participants visited the websites on sexual behaviour and sexually transmitted infections recommended in the travel health brochure. Conclusion: Only half of travel clinic visitors read information on sexual risk in the health brochure received in the clinic and none of them visited the related websites mentioned in the brochure. Further research to identify the most effective way to inform travellers about sexual risk is needed.